Decision Making Support in Wastewater Management: Comparative analysis of techniques and tools used in centralized and decentralized system layouts UDK 628.2 - Musiyarira, Harmony; Reynders, Cornelius Chris; Marjanovic, Prvoslav (Journal of Economic Development, Environment and People, 2012)
Wastewater management has been seen primarily as a technical and economic issue but it is now recognised that these are some of the elements in an array of other factors that affect sustainability of wastewater systems. Literature studies point out that municipal authorities have a general and long-standing tradition of using indicators in monitoring performance, reviewing progress and reporting the state of the environment as part of the regulatory enacted compliance. However, they have neglected other critical aspects of use of these indicators such as their input into the planning and decision making process. This research advocates for the use of sustainable indicators in a context based planning approach and the utilisation of Multi Criteria Decision Aid (MCDA) in a two step approach for comparative analysis and assessment of the sustainability of wastewater systems. The overall objective was to develop a methodology for wastewater systems selection and to produce a practical planning tool to aid in decision making for municipalities. Another objective was to provide recommendations for wastewater and sanitation management improvement in the case study area. The methodology consisted of comprehensive literature review, case study analysis, a review of the Decision Support Systems (DSS) in use and the development of the DSS for Gauteng Province. The full spectrum of viable wastewater or sanitation options was incorporated into the DSS. From the sustainability assessments carried out using Multi criteria decision analysis, one result showed that varying degrees of sustainability are obtainable with each treatment technology involved and decentralised technologies appear more sustainable. Based on the local context and indicators used in this research, the DSS results suggest that land treatment systems, stabilisation ponds and ecological treatment methods are more sustainable. One major finding from literature is that no technology is inherently sustainable on its own but is a function of the local context specifics. Since there is so much variation in social and economic needs within the areas; the overall results imply that a differential wastewater management approach should be employed with tailor made solutions resulting for each municipality or certain areas within a municipality.